Experimental implementation of fully controlled dephasing dynamics and synthetic spectral densities - Liu, Zhao-Di; Lyyra, Henri; Sun, Yong-Nan; Liu, Bi-Heng; Li, Chuan-Feng; Guo, Guang-Can; Maniscalco, Sabrina; Piilo, Jyrki (Nature communications, 2018)
Engineering, controlling, and simulating quantum dynamics is a strenuous task. However, these techniques are crucial to develop quantum technologies, preserve quantum properties, and engineer decoherence. Earlier results have demonstrated reservoir engineering, construction of a quantum simulator for Markovian open systems, and controlled transition from Markovian to non-Markovian regime. Dephasing is an ubiquitous mechanism to degrade the performance of quantum computers. However, all-purpose quantum simulator for generic dephasing is still missing. Here, we demonstrate full experimental control of dephasing allowing us to implement arbitrary decoherence dynamics of a qubit. As examples, we use a photon to simulate the dynamics of a qubit coupled to an Ising chain in a transverse field and also demonstrate a simulation of nonpositive dynamical map. Our platform opens the possibility to simulate dephasing of any physical system and study fundamental questions on open quantum systems. The study of dephasing dynamics have wide implications for understanding open systems evolutions and in particular decoherence of qubits. Here, the authors implement arbitrary qubit decoherence dynamics in a photonic simulator, also capable of implementing non-positive dynamical maps.